2022
DOI: 10.1158/0008-5472.can-22-0225
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Mapping and Targeting of Mitotic Pericentriolar Material in Tumors Bearing Centrosome Amplification

Abstract: Recent work has made it clear that pericentriolar material (PCM), the matrix of proteins surrounding centrioles, contributes to most functions of centrosomes. Given the occurrence of centrosome amplification in most solid tumors and the unconventional survival of these tumor cells, it is tempting to hypothesize that gel-like mitotic PCM would cluster extra centrosomes to defend against mitotic errors and increase tumor cell survival. However, because PCM lacks an encompassing membrane, is highly dynamic, and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…To explore the role of DNAJA2 in maintaining genome stability, particularly in maintaining mitotic integrity as DNAJA2 has been identified in the centrosome proteome 26 , 27 , we knocked out DNAJA2 ( DJ2 −/− ) in HeLa cells and monitored their mitotic division. Interestingly, we found that DNAJA2 knockout significantly elevated the production of multinuclear cells, and restoration of DNAJA2 expression in DJ2 −/− cells restored the multinuclear cell percentage to the normal level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the role of DNAJA2 in maintaining genome stability, particularly in maintaining mitotic integrity as DNAJA2 has been identified in the centrosome proteome 26 , 27 , we knocked out DNAJA2 ( DJ2 −/− ) in HeLa cells and monitored their mitotic division. Interestingly, we found that DNAJA2 knockout significantly elevated the production of multinuclear cells, and restoration of DNAJA2 expression in DJ2 −/− cells restored the multinuclear cell percentage to the normal level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the present study suggests that KIF11, KIF15, and KIFC1 play a pivotal role in regulating centrosome clustering after WGD in MP and BP cells, other kinesins are also likely to contribute to this process in different cell lines. In this connection, several kinesins have been implicated in regulating centrosome clustering after WGD, including KIF2C ( Goupil et al, 2020 ), KIF18A ( Cohen-Sharir et al, 2021 ; Marquis et al, 2021 ), KIF20A ( Xie et al, 2022 ), and KIF24 ( Mashima et al, 2022 ). However, it remains to be determined whether these and other kinesins participate in determining centrosome separation and spindle polarity after WGD in specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…A typical mammalian cell centrosome contains a centrally localized centriole pair in perpendicular orientation with each other and is surrounded by a centrosomal matrix called pericentriolar material (PCM). The mass spectrometric analysis of purified centrosomes shows a large number of proteins that include, α-tubulin, β-tubulin, γ-tubulin, γ-tubulin complex components 1-6, centrin 2 and 3, AKAP450, pericentrin/kendrin, ninein, pericentriolar material 1 (PCM1), centriolin, CLIP-associating proteins CLASP1 and CLASP2, EB1, centractin, myomegalin, Cdk1, dynein intermediate chain, dynein light chain, p150Glued, dynactin and Hsp73 [21].…”
Section: Distinct Orientation and Organization Of Microtubules In Epi...mentioning
confidence: 99%
“…Yet, our precise and in-depth understanding of how these dramatic changes in nucleation or originating sites of microtubules, its overall orientation inside the cells, and the resulting effect on cell adhesion and migration remains incomplete. Hyperactive MTOC and enhanced microtubule nucleation at the centrosome are increasingly recognized as hallmarks of cancer [21,74]. Clearly, a better molecular understanding of how microtubule organization impacts cell adhesion and migrations may open new avenues for cancer therapy.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%